Optimalisasi Kinerja Pegawai Melalui Pengembangan Budaya Learning Organization Berbasis Kompetensi Digital dengan SDM di Kantor Pajak Singosari - Ainin Wahyu Danti; Mariana Puspa Dewi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to optimize employee performance at the Singosari Tax Office through the development of a learning organization culture based on digital competence and human resources (HR). A qualitative approach was employed in this research using in-depth interviews, observations, and document analysis to collect data. The findings indicate that a strong learning organization culture enhances employees’ adaptation to technological changes and increasingly complex job demands. Developing digital competencies relevant to job needs is a key element in strengthening this culture. Additionally, systematic and continuous HR-based training has proven to enhance individual skills and team collaboration. The study’s implications suggest that optimizing employee performance requires not only advanced technology but also a cultural transformation toward continuous learning and digital competency enhancement